(untitled) (Canadian Medical Education Journal, 2016)
Background: There is growing recognition of the importance of physician leadership in healthcare. At the same time, becoming an effective leader requires significant training. While educational opportunities for practicing physicians exist to develop their leadership skills, there is a paucity of leadership opportunities for post graduate trainees. In response to this gap, both the Royal College of Physicians and Surgeons of Canada and the Association of Faculties of Medicine of Canada have recommended that leadership training be considered a focus in Post Graduate Medical Education (PGME). However, post-graduate leadership curricula and opportunities in PGME training programs in Canada are not well described. The goal of this study was to determine the motivation for PGME leadership training, the opportunities available, and educational barriers experienced by PGME programs at the University of Ottawa. Methods: An electronic survey was distributed to all 70 PGME Program Directors (PDs) at the University of Ottawa. Two PDs were selected, based on strong leadership programs, for individual interviews. Results: The survey response rate was 55.7%. Seventy-seven percent of responding PDs reported resident participation in leadership training as being “important,” while only 37.8% of programs incorporated assessment of resident leadership knowledge and/or skills into their PGME program. Similarly, only 29.7% of responding residency programs offered chief resident leadership training. Conclusions: While there is strong recognition of the importance of training future physician leaders, the nature and design of PGME leadership training is highly variable. These data can be used to potentially inform future PGME leadership training curricula.